2019
DOI: 10.1051/ctv/20193402091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cation exchange resin treatment of grape must on the chemical and sensory characteristics of base wines for sparkling wine

Abstract: Ion exchange resins are polymers with high physical and chemical stability, which, upon activation, acquire positive charge (H+) ions which interchange with existing cations during musts or wines treatment. The chemical composition of the grape must, and wines are highly affected by said modifications. This study aimed to evaluate the impact of the cationic resin treatments on the physicochemical and organoleptic characteristics of base white wines for sparkling wine production. Thus for, Chardonnay must was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Although examples of must treatments with cationic resins are scarce, similar results were obtained in previous works using cationic resins on wines (Mourgues, 1993;Walker et al, 2003;Ponce et al, 2018). Moreover, wines obtained from resin-treated musts (Cisilotto et al, 2019) showed an increase in total acidity and tartaric acid concentration proportional to resin-treatments.…”
Section: Physicochemical Parameters and Mineral Compositionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although examples of must treatments with cationic resins are scarce, similar results were obtained in previous works using cationic resins on wines (Mourgues, 1993;Walker et al, 2003;Ponce et al, 2018). Moreover, wines obtained from resin-treated musts (Cisilotto et al, 2019) showed an increase in total acidity and tartaric acid concentration proportional to resin-treatments.…”
Section: Physicochemical Parameters and Mineral Compositionsupporting
confidence: 80%
“…In the study by Tamasi et al (2018) the authors obtained similar results with the use of cation exchange resin in samples of dessert wines. In the study by Cisilotto et al (2019), lower susceptibility to browning overtime was reported in wines that had their must treated with ion exchange resins. In previous studies (Benıtez et al, 2002) showed reduced susceptibility to browning in white wines submitted to resin treatments.…”
Section: Physicochemical Parameters and Mineral Compositionmentioning
confidence: 96%
See 1 more Smart Citation